Does the COVID-19 Pandemic Impact on Audit Fee and Audit Report Lag? - Farhana, Farhana Farhana; Rahayu, Dewi Pudji; Nugroho, Arif Widodo (Jurnal Economia, 2025)
This article explains whether the COVID-19 pandemic affects Audit Fee and Audit Report Lag in the financial sector in 2018-2022. The sampling technique used was purposive sampling. The sample in this study were 59 financial sector companies listed on the Indonesia Stock Exchange (IDX), the research data totaled 295 samples. This study uses a panel regression model to estimate the extent to which the COVID-19 pandemic predicts changes in Audit Fee and Audit Report Lag. The results of this study indicate that the COVID-19 pandemic has a positive effect on Audit Fee and Audit Report Lag. There is evidence that the COVID-19 pandemic has an influence on audit quality. The results have significant policy implications, especially from the perspective of the Indonesian Public Accountants Association (IAPI), to warn auditors about the increased audit risk caused by the COVID-19 pandemic and the need to compensate with quality audits.